Caracterização físico-química de frutos de tangerineira 'ponkan' (Citrus reticulata Blanco), cultivada em mossoró/rn, sob armazenamento refrigerado - Celedonio, Wilma Freitas (Universidade Federal Rural do Semi-Árido, 2017)
Brazil is the third largest producer of fruit, behind only China and India, and currently the country is the largest producer of citrus, with emphasis on orange and tangerine. The objective of this work is to evaluate the physico-chemical characteristics of 'Ponkan' tangerine (Citrus reticulata Blanco), cultivated in Mossoró-RN, under refrigerated storage. The experiment was conducted in a completely randomized experimental design in subdivided plots (3 x 5), with three (3) hull colorations in the plot [predominantly green (PV), predominantly yellow (PA) and fruits of time (DV)] and 5 (five) storage times in the subplot (0, 7, 14, 21, and 28 days after harvest). After harvesting the fruits were transported to the Post Harvest Laboratory of the Federal Rural Semi-Arid University, and then selected five fruits by uniformity of size and shell color for each of the storage times. Physical analyzes were performed: loss of mass, longitudinal and transverse diameter of the fruit, house thickness, juice volume, seed weight, bagasse weight, bark weight and staining; and chemical analyzes: total soluble solids, pH, vitamin C, titratable acidity and total sugars. The 'Ponkan' mandarin fruits produced in Mossoró - RN, harvested in three stages of maturation, present physicochemical characteristics that meet the market requirement and can be commercialized even after 28 days of storage.
Monografia
Keywords: Pós-colheita; Fruticultura; Citros; Semiárido; Postharvest; Fruit growing; Citrus; Semiarid region; CIENCIAS AGRARIAS::AGRONOMIA